Clinical features, bacteriology of endotracheal aspirates and treatment outcomes of patients with chronic obstructive pulmonary disease and community-acquired pneumonia in an intensive care unit in Taiwan with an emphasis on eosinophilia versus non-eosinophilia: a retrospective case–control study. Issue 9 (11th September 2018) - Huang, Wei-Chang; Lee, Ching-Hsiao; Wu, Ming-Feng; Huang, Chen-Cheng; Hsu, Cheng-Hui; Chen, Hui-Chen; Hsu, Jeng-Yuan; Huang, Chieh-Chen
Abstract : Objectives: The clinical implications of blood eosinophil level in patients with chronic obstructive pulmonary disease (COPD) and community-acquired pneumonia (CAP) requiring invasive mechanical ventilation (IMV) and intensive care unit (ICU) admission are still unknown. Thus, this study aimed to compare the features of such patients with and without blood eosinophilia. Design: This was a retrospective case–control study. Setting: An ICU of a medical centre in central Taiwan. Participants: A total of 262 patients with COPD and CAP requiring IMV and ICU admission. Results: Of all participants (n=262), 32 (12.2%) had an eosinophil percentage (EP) >2% and 169 (64.5%) had an absolute eosinophil count (AEC) >300 cells/µL. Regardless of whether 2% or 300 cells/µL was used as a cut-off value, the eosinophilia group were slightly older (years) (82.9±5.4 vs 78.1±9.1, p=0.000 and 79.2±8.4 vs 77.6±9.6, p=0.246, respectively), and had a higher forced expiratory volume in 1 s/forced vital capacity (%) (56.0±8.0 vs 51.3±11.6, p=0.005 and 53.1±11.2 vs 49.5±11.2, p=0.013, respectively), less severe spirometric classification (p=0.008 and p=0.001, respectively), and lower white cell count 10 9 /L (8.8±3.2 vs 11.1±4.9, p=0.009 and 10.3±4.4 vs 11.8±5.3, p=0.017, respectively) than the non-eosinophilia group. The bacteriology of endotracheal aspirates showed that Pseudomonas aeruginosa and other gram-negative bacilli were the most common organisms in all study groups. Participants with an EP >2% had a shorter ICU length of stay (OR=12.13, p=0.001) than those with an EP ≤2%, while an AEC >300 cells/µL was not associated with any in-ICUoutcomes. Conclusions: The results of this study have significant clinical implications and should be considered when making treatment decisions for the management of patients with COPD and CAP requiring IMV and ICU admission.